Belastungen und Verletzungen des Kniegelenkes im Alpinen Ski-Hochleistungssport - Eine Status-quo-Analyse unter spezieller Fokussierung auf das vordere Kreuzband - Brucker, P. U.; Spitzenpfeil, P.; Huber, A.; Waibel, K.; Maier, W. (Sport-Orthopädie - Sport-Traumatologie, 2011)
In competitive alpine ski racing, the knee joint is exposed to exalted loadings and therefore at high risk for overloadings, which is mirrored by the persistently high incidence of knee injuries. However, causative factors and mechanisms for specific knee injuries, e.g. anterior cruciate ligament (ACL) ruptures, are multifactorial. Indeed, previously performed strategies for prevention of especially ruptures of the ACL have not been successfully implemented in professional alpine ski racing to reduce the incidence of these injuries. It seems mandatory in the future, that novel approaches at different levels must be considered to overcome these complex problems.